The prevalence of human papillomavirus genotypes among patients with sexually transmitted HPV in north Iran - Sajad Salehi; Rana Rafiei; Reyhaneh Ghadarjani; Kaveh Gharaei Nejad (Elsevier, 2024)
Objective: Given the high prevalence of sexually transmitted human papillomavirus (HPV) and the increasing number of individuals affected by this disease, the present study investigated the frequency of HPV genotypes in patients with sexually transmitted HPV. Methods: In this cross-sectional study, samples of 2534 patients who were diagnosed with sexually transmitted HPV from 2016 to 2023, were examined for HPV genotype in Rasht, Iran. HPV infection was confirmed by performing a polymerase chain reaction (PCR), and samples were genotyped for classification. Also, data on the age and gender of patients were recorded, and all data was analyzed using SPSS version 22 with a significant level <0.05. Results: The mean age of the patients was 33.8 ± 13.34 years, and 89.1 % were females. A total number of 4739 samples from 2534 patients were genotyped. About 52.2 % of HPV genotypes were low-risk HPV, and 47.8 % were high-risk HPV. HPV6 exhibited the highest prevalence in the low-risk category, while HPV16 showed the highest prevalence in the high-risk category. The frequency of HPV was significantly different among patients according to age and gender (P < 0.05). Conclusion: Due to the high prevalence of sexually transmitted high-risk HPV, vaccination programs may lead to a reduction in sexually transmitted infections and alleviate the associated economic and social burdens.